ANALISA KADAR FENOLIK EKSTRAK ETANOL DAUN NANGKA (Artocarphus heterophyllus) DENGAN MENGGUNAKAN INSTRUMENTASI SPEKTROSCOPY UV-VIS - Effendi S, Mahral (Program Studi S1 Farmasi, STIKES Senior, Medan, 2024)
Research has been carried out to analyze the phenolic content of the ethanol extract of jackfruit leaves by carrying out the initial stages, namely selecting homogeneous jackfruit leaves and forming simplicia. The simplicia formed was then characterized microscopically and macroscopically and a phytochemical screen test was carried out to determine the active secondary metabolite ingredients contained therein. The method used in the secondary metabolite extraction process uses maceration with ethanol solvent, measuring phenolic content using a colorimetric method using UV-Vis spectrophotometry at a wavelength of 775 nm. Phenolic content was previously obtained by forming a standard curve to obtain a linear regression equation. The results of the analysis show that the linear regression equation formed is y = 0.001x + 0.0048. The results of sample analysis in this research show that the Phenolic concentration value is 60 mg GAE/g Jackfruit leaf ethanol extract.